Heterogeneity in Induction Level, Infection Ability, and Morphology of Shiga Toxin-Encoding Phages (Stx Phages) from Dairy and Human Shiga Toxin-Producing Escherichia coli O26:H11 Isolates - Bonanno, Ludivine (Appl Environ Microbiol, 2016)
Shiga toxin (Stx)-producing Escherichia coli (STEC) bacteria are foodborne pathogens responsible for diarrhea and hemolytic-uremic syndrome (HUS). Shiga toxin, the main STEC virulence factor, is encoded by the stx gene located in the genome of a bacteriophage inserted into the bacterial chromosome. The O26:H11 serotype is considered to be the second-most-significant HUS-causing serotype worldwide after O157:H7. STEC O26:H11 bacteria and their stx-negative counterparts have been detected in dairy products. They may convert from the one form to the other by loss or acquisition of Stx phages, potentially confounding food microbiological diagnostic methods based on stx gene detection. Here we investigated the diversity and mobility of Stx phages from human and dairy STEC O26:H11 strains. Evaluation of their rate of in vitro induction, occurring either spontaneously or in the presence of mitomycin C, showed that the Stx2 phages were more inducible overall than Stx1 phages. However, no correlation was found between the Stx phage levels produced and the origin of the strains tested or the phage insertion sites. Morphological analysis by electron microscopy showed that Stx phages from STEC O26:H11 displayed various shapes that were unrelated to Stx1 or Stx2 types. Finally, the levels of sensitivity of stx-negative E. coli O26:H11 to six Stx phages differed among the 17 strains tested and our attempts to convert them into STEC were unsuccessful, indicating that their lysogenization was a rare event.